Psychotropic medication use and risk of adverse cardiovascular events in women with suspected coronary artery disease: outcomes from the Women's Ischemia Syndrome Evaluation (WISE) study. Issue 23 (6th August 2009) - Krantz, D S; Whittaker, K S; Francis, J L; Rutledge, T; Johnson, B D; Barrow, G; McClure, C; Sheps, D S; York, K; Cornell, C; Bittner, V; Vaccarino, V; et al.
Abstract : Objective: This study investigated the relation between psychotropic medication use and adverse cardiovascular (CV) events in women with symptoms of myocardial ischaemia undergoing coronary angiography. Method: Women enrolled in the Women's Ischemia Syndrome Evaluation (WISE) were classified into one of four groups according to their reported antidepressant and anxiolytic medication usage at study intake: (1) no medication (n = 352); (2) anxiolytics only (n = 67); (3) antidepressants only (n = 58); and (4) combined antidepressant and anxiolytics (n = 39). Participants were followed prospectively for the development of adverse CV events (for example, hospitalisations for non-fatal myocardial infarction, stroke, congestive heart failure and unstable angina) or all-cause mortality over a median of 5.9 years. Results: Use of antidepressant medication was associated with subsequent CV events (HR 2.16, 95% CI 1.21 to 3.93) and death (HR 2.15, 95% CI 1.16 to 3.98) but baseline anxiolytic use alone did not predict subsequent CV events and death. In a final regression model that included demographics, depression and anxiety symptoms, and risk factors for cardiovascular disease, women in the combined medication group (that is, antidepressants and anxiolytics) had higher risk for CV events (HR 3.98, CI 1.74 to 9.10, p = 0.001 and all-cause mortality (HR 4.70, CI 1.7 to 2.97, p = 0.003) compared to those using neither medication. Kaplan-Meier survival curves indicated that there was a significant difference in mortality among the four medication groups (p = 0.001). Conclusions: These data suggest that factors related to psychotropic medication such as depression refractory to treatment, or medication use itself, are associated with adverse CV events in women with suspected myocardial ischaemia.